2014
DOI: 10.1001/jamaophthalmol.2014.266
|View full text |Cite
|
Sign up to set email alerts
|

Acute Retinal Necrosis Associated With Epstein-Barr Virus

Abstract: cute retinal necrosis (ARN) is a syndrome characterized by progressive intraretinal inflammation and necrosis. The clinical diagnosis is frequently supported by the identification of the causative infectious agent, most commonly varicella-zoster virus (VZV), though herpes simplex virus (HSV) types 1 and 2, cytomegalovirus, and Epstein-Barr virus (EBV) have also been implicated. 1,2 Epstein-Barr virus, a double-stranded DNA virus transmitted by oral secretions, infects more than 90% of humans. 3 IMPORTANCE Acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 5 publications
3
43
0
Order By: Relevance
“…[ 12 ] EBV-associated ARN has also been shown histopathologically in one case, although clinically, this case appeared to involve much more extensive hemorrhagic retinitis than in typical ARN. [ 13 ] VZV and HSV-1 associated ARN are more commonly found in older and middle-aged patients whereas HSV-2 associated ARN is more common in children and young adults. [ 1416 ]…”
Section: Viral Uveitismentioning
confidence: 99%
“…[ 12 ] EBV-associated ARN has also been shown histopathologically in one case, although clinically, this case appeared to involve much more extensive hemorrhagic retinitis than in typical ARN. [ 13 ] VZV and HSV-1 associated ARN are more commonly found in older and middle-aged patients whereas HSV-2 associated ARN is more common in children and young adults. [ 1416 ]…”
Section: Viral Uveitismentioning
confidence: 99%
“…There is no known racial or gender predilection . EBV has infrequently been implicated as a causative agent and is usually found in conjunction with VZV or immunocompromise . CMV is a rare cause of ARN …”
Section: Acute Retinal Necrosismentioning
confidence: 99%
“…It has been identified using PCR from the ocular fluids of eyes with anterior uveitis, vitritis, vasculitis and retinitis, and in 70% of normal cadaveric eyes . Reports have also identified its presence in eyes with ARN, mostly concomitantly with HSV or VZV, though there have also been cases where it was the only identified pathogen . Schaal et al demonstrated EBV DNA in the retinal cells of a patient with ARN, supporting its role in disease rather than as an indicator of lymphocyte migration.…”
Section: Epstein‐barr Virus Retinitismentioning
confidence: 99%
“…It has been suggested that the pathogenesis is closely tied to viral infection, most commonly with varicella-zoster virus (VZV) and herpes simplex virus (HSV), though there are some cases where the infectious agent has been cytomegalovirus (CMV) or Epstein-Barr virus (EBV) [3]. Although EBV infection in ARN is rarely found alone, but rather co-existing with VZV infection [4], a recent report has demonstrated EBV as the only virus in the retina of a patient with ARN [5]. The most common therapeutic approach for ARN is anti-viral therapy immediately after diagnosis [2]; in previous reports, early vitrectomy with intravitreal lavage using anti-viral medication was associated with a lower incidence of secondary retinal detachment [3].…”
Section: Introductionmentioning
confidence: 99%